Study on the dispersion, adsorption and early hydration behavior of cement pastes containing multi-armed polycarboxylate superplasticizers. Issue 2 (28th January 2020) - Wang, Kun; Pang, Hao; Huang, Hao; Song, Linxia; Huang, Jianheng; Zhao, Yangyang
Abstract: Multi-armed polycarboxylate superplasticizers (SPCEs) were prepared via esterification-copolymerization in aqueous media from various polyols (including glycerol, xylitol and mannitol), acrylic acid (AA) and isopentenyl oxy polyethylene glycol ether (TPEG). The structures of the SPCEs (SPCE-prop, SPCE-pent and SPCE-hex bearing three, five and six arms, respectively) were characterized by NMR and GPC. The influences of the SPCEs on the fluidity, adsorption and early hydration behaviors of cementitious systems were investigated in detail and are discussed herein. Experimental results indicated that as the number of pendant arms increased, the dispersion performance, compactness of the cement microstructures and set retarding effects increased initially and subsequently decreased (SPCE-pent offered the best performance). This effect was primarily due to the synergistic effects of steric hindrance and electrostatic repulsions. Further results indicated that SPCE-pent can be used as a high-range delivery admixture to produce high performance concrete. GRAPHICAL ABSTRACT: